The Effectiveness of South Sulawesi Local Culture-Based Aerobic Dances on Cardiovascular Endurance and Flexibility in Young Women - Poppy Elisano Arfanda; Ians Aprilo; M. Adam Mappaompo; Arimbi; Retno Farhana Nurulita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to investigate the impact of South Sulawesi's local culture-based aerobic dances on enhancing cardiovascular endurance and flexibility. The research method used was a quasi-experimental design with a pretest-posttest group approach. The research subjects consisted of 20 healthy young women aged 18–25 years. The intervention program was conducted over eight weeks, with participants attending three sessions per week, each lasting 45 minutes. The aerobic dance program incorporated traditional South Sulawesi dance movements and music. Cardiovascular endurance was measured using the Beep Test, while flexibility was assessed through the Sit and Reach test. The results showed a significant increase in both variables with p < 0.05. These findings indicate that local culture-based aerobic dances are effective in enhancing physical fitness while providing a more meaningful and enjoyable exercise experience through cultural engagement. This research provides a scientific foundation for developing physical training programs based on local wisdom that can be implemented in community-based physical activities.